Weakly nonlinear boundary-value problems for operator equations with pulse influence - Boichuk, О. A.; Zhuravlev, V. F.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the problem of finding conditions of solvability and algorithms for construction of solutions of weakly nonlinear boundary-value problems for operator equations (with the Noetherian linear part) with pulse influence at fixed times. The method of investigation is based on passing by methods of the Lyapunov—Schmidt type from a pulse boundary-value problem to an equivalent operator system that can be solved by iteration procedures based on the fixed-point principle.